Relationship of Microalbuminuria with Ischemic Heart Disease in Nondiabetic Subjects - Ankit Jain; Vikas Kumar; Kunal Shrimal (Heart Views)
Background: Microalbuminuria has been established as a marker for increased cardiovascular risk in diabetic patients. Nonetheless, its correlation with ischemic heart disease (IHD) among individuals without diabetes has received limited attention. The current study was performed to explore the potential link between microalbuminuria and IHD in nondiabetic subjects. Methodology: During 2 years, a case–control study was executed, encompassing 100 individuals without diabetes who had IHD as cases, and an equal number of 100 non-IHD controls. Microalbuminuria levels were evaluated alongside diverse cardiovascular risk factors in both sets. IBM-SPSS version 25.0 was used for statistical analysis. Results: The mean age, gender distribution, and body mass index were similar between the cases and controls. There was a higher prevalence of smokers and alcohol users among the cases compared to controls. In addition, a positive family history of IHD was more prevalent in the case group. In the case group, the mean values of systolic blood pressure, diastolic blood pressure, mean arterial pressure, fasting blood glucose, cholesterol, low-density lipoprotein (LDL), serum creatinine, and urine albumin levels were notably elevated compared to the control group. A significant increase in microalbuminuria levels in the case group was observed. Conclusion: The results reveal a substantial link between microalbuminuria and IHD in individuals without diabetes. Microalbuminuria was independently correlated with major cardiovascular risk factors, including alcohol and cigarette use, and higher levels of cholesterol, LDL, and serum creatinine. These findings suggest that urine albumin measurements could serve as an early marker for identifying cardiovascular disease risk factors and potentially aid in preventive interventions in the general population.